2011
DOI: 10.1111/j.1600-6143.2011.03515.x
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer after Heart Transplantation: Results from a Large Multicenter Registry

Abstract: In this study we analyzed Spanish Post-HeartTransplant Tumour Registry data for adult heart transplantation (HT) patients since 1984. Median post-HT follow-up of 4357 patients was 6.7 years. Lung cancer (mainly squamous cell or adenocarcinoma) was diagnosed in 102 (14.0% of patients developing cancers) a mean 6.4 years post-HT. Incidence increased with age at HT from 149 per 100 000 person-years among under-45s to 542 among over-64s; was 4.6 times greater among men than women; and was four times greater among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
3
14
1
Order By: Relevance
“…We also found that organ transplant recipients with de novo lung cancer diagnoses were more likely to present with early stage lung cancer than non-transplanted patients. This differs from previous studies of lung cancer in organ transplant recipients that reported higher rates of late stage lung cancers(11, 26, 28). Two of those studies did not have comparison groups, and all were much smaller than the current analysis, and not population-based.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also found that organ transplant recipients with de novo lung cancer diagnoses were more likely to present with early stage lung cancer than non-transplanted patients. This differs from previous studies of lung cancer in organ transplant recipients that reported higher rates of late stage lung cancers(11, 26, 28). Two of those studies did not have comparison groups, and all were much smaller than the current analysis, and not population-based.…”
Section: Discussioncontrasting
confidence: 99%
“…We found higher rates of NSCLC with squamous cell histology in transplant recipients, a finding also reported in prior studies(26, 28). A possible explanation for the predominance of squamous cell cancers in patients who received transplants is that chronic immunosuppression diminishes T-cell mediated control of viral infections.…”
Section: Discussionsupporting
confidence: 91%
“…Noncutaneous solid tumors arose in 14.3% of patients with PT (three considered relapsing malignancies [two colon carcinomas, one bladder carcinoma]) and 9.3% of patients with NPT. Lung cancer was the most common one, in agreement with data from a study assessing post‐HT lung cancer incidence and other studies showing lung cancer as one of the most frequently developing solid tumors in HT recipients . Hematologic tumors developed in 3.9% (three of 77) of PT patients (one tumor was multiple myeloma, considered a relapsing malignancy) and 2.4% (108 of 4484) of NPT patients.…”
Section: Discussionsupporting
confidence: 87%
“…We know of no studies in the transplant literature that have reported this association 45. Both smoking and medication nonadherence are important known risk factors for poor clinical outcomes following HTx 2, 46…”
Section: Discussionmentioning
confidence: 99%